KOMUNIKASI INTERPERSONAL GURU DAN ORANG TUA DALAM MENCEGAH KENAKALAN REMAJA PADA SISWA (STUDI DESKRIPTIF PADA SISWA KELAS XI SMA KOLOMBO SLEMAN) - Mustika Chairani; Ida Wiendijarti; Dewi Novianti (Jurnal Ilmu Komunikasi, 2009)
Interpersonal Communication has a significant role on the level of juvenile delinquency. This is reflected by studies that showing interpersonal communication can improve, giving motivation between students. The method adapted in this study with a qualitative descriptive study. The subjects is Colombo Yogyakarta high school students were 12 students from the total population of 88. Determination of informants is based on consideration the wealth of information. Everett M Rogers approach is used as a bookmark in communications where the idea is transferred from one source to another source with the intent to change behavior. In this research, Newcom ABX model adapted to describe aspects of the emergence of juvenile delinquency. While Osgood-Schramm circular model is able to explain the results of this study that the feedback does not occur dynamically. The objectives in these research are not effective on interpersonal communication. It arises from the students that are lazy, introvert character, ansupported parents, as well as differences in arguments between students, teachers and parents.